2021
DOI: 10.1038/s41586-021-04345-x
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic responses to SARS-CoV-2 infection in children and adults

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
271
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(293 citation statements)
references
References 91 publications
20
271
2
Order By: Relevance
“…In this study, the lower level of CRP and IL-6 was observed in the younger children, which may indicate a milder overall inflammatory response and a good prognosis in this population ( Liu et al., 2020 ). The younger children in the current study reported a higher lymphocyte count than their counterparts, which might be due to different physiological status ( Yoshida et al., 2021 ) and different disease conditions between them ( Viau & Zouali, 2005 ; Bieberich et al., 2021 )…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, the lower level of CRP and IL-6 was observed in the younger children, which may indicate a milder overall inflammatory response and a good prognosis in this population ( Liu et al., 2020 ). The younger children in the current study reported a higher lymphocyte count than their counterparts, which might be due to different physiological status ( Yoshida et al., 2021 ) and different disease conditions between them ( Viau & Zouali, 2005 ; Bieberich et al., 2021 )…”
Section: Discussionmentioning
confidence: 60%
“…As for the mild disease status observed in the younger children, a recent study reported that the expression of ACE-2 receptor is lower in the upper and lower airways of children than in the nasal epithelium of healthy adults, resulting in a lower risk of SARS-Cov-2 infection in this population ( Yoshida et al., 2021 ). Furthermore, the milder condition in the younger patient cohort may be closely related to the potent innate immunity of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering trachea RNA-seq data was collected at day 14 post-inoculation in our study, when viral loads were not detectable anymore, it is possible that levels of some ISGs are upregulated in infants at baseline compared to adults. Indeed, this has been demonstrated in multiple pediatric cohorts where ISGs (40) and cytokines and chemokine genes (41) were increased in SARS-CoV-2-uninfected children compared to adults. Upon SARS-CoV-2 infection, children’s IFN-α responses were greater in multiple immune cell subsets including NK CD56 low , NKT cells, neutrophils, CXCL10+ monocytes and some CD8+ T cell subsets (40).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, this has been demonstrated in multiple pediatric cohorts where ISGs (40) and cytokines and chemokine genes (41) were increased in SARS-CoV-2-uninfected children compared to adults. Upon SARS-CoV-2 infection, children’s IFN-α responses were greater in multiple immune cell subsets including NK CD56 low , NKT cells, neutrophils, CXCL10+ monocytes and some CD8+ T cell subsets (40). These data suggest the IFN response in children is pre-activated in epithelial cells of the upper airways and stronger in immune cell subsets compared to adults.…”
Section: Discussionmentioning
confidence: 90%